Әл-Фараби метафизикасындағы Бірінші Болмыстың материалдық емес мәні - A., Tuleubekov; B., Meirbayev; A., Doskozhanova (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2021)
This article reveals the non-material nature of the First Existence in the metaphysical system of Abu Nasr al-Farabi. The purpose of this analysis is to describe the evidence base that al-Farabi gives in order to identify the immateriality of the First Being. The system of argumentation of the immateriality of the First Being is part of the description of the perfection of the First Being, which al-Farabi presents within the framework of general cosmology. Justifying immateriality, al-Farabi basically follows the Aristotelian interpretation. However, he added a lot from the worldview of the Neoplatonists. As you know, the Neoplatonists paid great attention to emanation. According to the Neoplatonists, the Supreme Reason exists everywhere, and He is eternal in time. Al-Farabi borrowed this idea from the Neoplatonists, thanks to which he expanded his cosmology. In this regard, al-Farabi is a universal interpreter who synthesized the view of the Peripatetics and Neoplatonists into a single metaphysical system. At the same time, al- Farabi created his own cosmological system. It contains both the ideas of ancient and medieval Islamic scholars and their own vision of heavenly metaphysics. For a deep understanding of the nature of bodily substances, al-Farabi divided the heavenly structure into two levels. The first level – above moon – covers the ontology of the First Being and the sphere of celestial intellects. The second level – sublunary – describes everything that is in the sphere of the Earth. Thus, the idea of the immaterial nature of the First Being is an important part of his deep metaphysical system. Key words: the First Being, metaphysics, material world, intangible nature.